Cord Blood Biomarkers Predict Psoriasis Many Years Before Diagnosis: A Prospective Birth Cohort Study - Das, Debojyoti; Ludvigsson, Johnny (Archives of Clinical and Biomedical Research, 2025)
Background: This study aimed to identify biomarkers that can serve as putative predictors for different groups based on psoriasis diagnosis, onset, and severity, with the clinical implication of decreasing the risk of developing the disease. Material and Methods: Multiple protein biomarkers were assessed in cord blood from 115 psoriasis affected cases and 220 healthy controls in ABIS (All Babies in Southeast Sweden) by proximity extension assay (PEA). Results: IFNGR1, COLEC12, and TNFRSF11B had higher expression in cases while 50 had a higher expression in controls, especially STX.8, COL9A1, HLA-E, PLXNA4, RAB37, EDAR, and CD84. Gene Ontology enrichment with all annotated proteins reveals that IFNGR1 is enriched in GO terms, whereas TNFRSF was enriched in GO terms. The same two proteins were found significant using ANOVA with sex, and gestational age as covariates and same GO terms were enriched. Number of significantly different biomarkers in the onset groupings were 28, 57, and 41 for "healthy - post puberty psoriasis”, “healthy - pre puberty psoriasis" and "post puberty psoriasis - pre puberty psoriasis", respectively. Similarly, we found 70, 24, and 61 differentially expressed proteins for “healthymild”, “healthy-severe”, and “mild-severe” comparisons. Conclusions: Several proteins were increased already in cord blood of individuals who later developed psoriasis, but even more proteins usually related to immune system and/or skin structure were significantly reduced in these individuals. This suggests that factors already during pregnancy may play a role for development of psoriasis. However, we found no significant association to environmental factors during pregnancy.